Arabidopsis LEC1 and LEC2 Orthologous Genes Are Key Regulators of Somatic Embryogenesis in Cassava - Brand, Alejandro; Quimbaya, Mauricio; Tohme, Joseph M.; Chavarriaga-Aguirre, Paul (Frontiers Media, 2019)
High genotype-dependent variation in friable embryogenic callus (FEC) induction and subsequent somaclonal variation constitute bottlenecks for the application and scaling of genetic transformation (GT) technology to more farmer- and industry-preferred cassava varieties. The understanding and identification of molecular factors underlying embryogenic development in cassava may help to overcome these constraints. Here, we described the Arabidopsis thaliana LEAFY COTYLEDON (LEC) LEC1 and LEC2 orthologous genes in cassava, designated as MeLEC1 and MeLEC2, respectively. Expression analyses showed that both, MeLEC1 and MeLEC2, are expressed at higher levels in somatic embryogenic (SE) tissues in contrast with differentiated mature tissues. The rapid expression increase of MeLEC genes at early SE induction times strongly suggests that they are involved in the transition from a somatic to an embryonic state, and probably, in the competence acquisition for SE development in cassava. The independent overexpression of the MeLEC genes resulted in different regenerated events with embryogenic characteristics such as MeLEC1OE plants with cotyledon-like leaves and MeLEC2OE plants with somatic-like embryos that emerged over the surface of mature leaves. Transcript increases of other embryo-specific regulating factors were also detected in MeLECOE plants, supporting their mutual interaction in the embryo development coordination. The single overexpression of MeLEC2 was enough to reprogram the vegetative cells and induce direct somatic embryogenesis, which converts this gene into a tool that could improve the recovery of transformed plants of recalcitrant genotypes. The identification of MeLEC genes contributes not only to improve our understanding of SE process in cassava, but also provides viable alternatives to optimize GT and advance in gene editing in this crop, through the development of genotype-independent protocols